Aspects of coordination by junction in Old Romanian - Ștefan Găitănaru (Diacronia, 2016)
The approach of coordination by junction in a diachronic perspective aimed at establishing the discursive values of the connectors, in the integrated frame of these syntactic relation patterns, and the manner in which the literary norm selected the elements of each subclass throughout time. This study relies on statistical information and that referring to the dialectal areas distribution collected from recent studies in this field, and provides various examples from the first three centuries of Romanian texts, thus highlighting the continuity of this process. The main objective of the research was the integration in the coordination system of the patterns which the researches have mostly neglected so far, even in the Romanian contemporary language. Concerning the adversative relation, the present research also describes the coordination in periodic complex sentences such as concessive and conditional coordination (the latter unreported in contemporary Romanian) as evidence of spoken Latin – Romanian continuity.